(untitled) (Research, Society and Development, 2021)
This study aimed to understand the perception of pregnant women in relation to prenatal care in Basic Health Units. This is a qualitative descriptive study, carried out with pregnant women undergoing prenatal care in the Primary Health Care of a municipality. from the interior of Bahia. Data collection was done through a semi-structured interview with a script composed of questions about the theme, after signing the Informed Consent Term. For data analysis, the Thematic Content Analysis technique proposed by Bardin was used. The research respected the ethical and scientific aspects in accordance with Resolution No. 466 of 2012 and No. 510/16 of the National Health Council. Through content analysis, the results were grouped into three structured categories: The pregnant woman’s perception of prenatal care received; The care provided by the nurse (o) and her contribution to the process of coping with changes related to pregnancy; Nursing consultation and psychosocial assistance as contributors to successful prenatal care. It is understood that, given the perceptions of pregnant women, the care provided by the nurse in the prenatal program includes the reception, care actions, procedures and active listening to them, covering, above all, the individuality of each pregnant woman during consultations, and the biopsychosocial aspects inherent to the context of life in which they are inserted.